Impact of Psychological Factors on Investment Decisions in Nepalese Share Market: A Mediating Role of Financial Literacy - Subedi, Dhruba; Bhandari, Dilli Ram (Cattleya Darmaya Fortuna, 2024)
The Nepalese stock market is characterized by emerging market dynamics and notable volatility. It is influenced by factors such as regulatory developments, economic conditions, and investor sentiment, shaping its growth trajectory and investor behavior. This study examines the influence of psychological factors on investment decisions within the Nepalese share market, emphasizing the mediating role of financial literacy. To achieve the stated objective, data were collected from the primary source using a structured questionnaire administered through random sampling technique. The respondents comprised 410 individual investors inside the Kathmandu Valley. The SmartPLS 4.0 was used to analyze the structural relationships within the proposed theoretical model. The findings of this study validated the set hypotheses that psychological factors have positive and significant effect on investment decisions among the investors in Nepalese share market. In the context of Nepal, where the share market is characterized by volatility and emerging market dynamics, these psychological biases often lead to suboptimal investment choices. Findings indicate that investors with higher financial literacy levels are better equipped to mitigate the adverse effects of psychological biases, leading to more rational and informed investment decisions. The study highlights the critical need for enhanced financial education programs to empower investors and improve overall market efficiency. By understanding the interplay between psychological factors and financial literacy, policymakers and financial institutions can develop targeted strategies to foster a more stable and resilient investment environment in Nepal.